Translating the Health Belief Model into Contextual Community Intervention: A Study of Proper Hygiene Practices of Mothers of Children with Diarrhea - Yuniarti, Kwartarini W. (ANIMA Indonesian Psychological Journal, 2010)
Diarrhea remains a serious burden for children in developing countries, and remains a leading cause of childhood morbidity and mortality. The health belief model (HBM) is frequently used in explain- ing health behaviours. This study used HBM and translated it into community understanding to gain local perspective of mothers of children with diarrhea. A qualitative approach using focus group dis- cussions was conducted. A community model was then developed using local data. Data showed that mothers believe in two kinds of diarrhea: diarrhea as a disease and diarrhea as a part of the deve- lopmental process. The contextual community model explain the HBM in a different frame of theo- retical explanation model, which was developed in different setting of culture, can not be simply applied in the community without undertaking field verification, as conducted in this study. Detailed results and discussion are presented and proposals for a culture-sensitve intervention approach were proposed. Diare merupakan permasalahan serius di negara berkembang dan bahkan merupakan penyebab utama mortalitas dan morbiditas balita. Health belief model (HBM) sering dipakai untuk menjelaskan perilaku kesehatan. Studi awal ini memakai Health Belief Model untuk mengetahui pemahaman masyarakat tentang permasalahan diare dan perilaku kebersihan. HBM dalam pemetaan teoretis diverifikasi di komunitas untuk menguji presisi model secara kualitatif. Diskusi kelompok terarah dipakai dalam eksplorasi kualitatif. Data menunjukan bahwa model diare di komunitas studi berbeda dengan model biomedis. Para Ibu memercayai adanya dua jenis diare, diare sebagai penyakit dan diare yang merupakan bagian dari tumbuh kembang anak. Dapat disimpulkan bahwa model komunitas kontekstual berbeda dengan model biomedis. Bahasan terinci disajikan dalam artikel ini. Program intervensi yang peka kultur setempat diajukan sesuai dengan hasil penelitian ini.